Respuesta :
For us to get the solutions of the given function, we let f(x) be equal to zero and solve for the values of x.
f(x) = 12x² - 13x + 3 = 0
To get the two values of roots, a and b, we use the concepts presented below.
a + b = -B/A
ab = C/A
Substituting the known values,
a + b = -(-13/12) = 13/12
ab = 3/12
The values of a and b from the equation are 3/4 and 1/3, respectively.
The solution set then becomes {3/4, 1/3}.
f(x) = 12x² - 13x + 3 = 0
To get the two values of roots, a and b, we use the concepts presented below.
a + b = -B/A
ab = C/A
Substituting the known values,
a + b = -(-13/12) = 13/12
ab = 3/12
The values of a and b from the equation are 3/4 and 1/3, respectively.
The solution set then becomes {3/4, 1/3}.